2021
DOI: 10.1177/1071181321651051
|View full text |Cite
|
Sign up to set email alerts
|

Internet Accessibility for Blind and Visually-Impaired Users: An Evaluation of Official U.S. State and Territory COVID-19 Websites

Abstract: During the COVID-19 pandemic, most health information was moved to an online format for easier dissemination. However, many of these health websites may not be accessible to users who are visually impaired, such as people who use screen readers and magnifiers. This study aimed to test the accessibility of 55 U.S. state and territory COVID-19 websites using 3 automated accessibility checker tools (MAUVE++, CynthiaSays, and AChecker). The homepage, testing, and vaccine pages for each state/territory were tested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…Lectures incorporating this word include "User Experience and Evaluation." This word appeared frequently in conference proceedings titles such as "Tele-Technology Evaluation and User Testing with Persons Aging with Long-Term Mobility Disabilities" (Wu et al, 2021), "Internet Accessibility for Blind and Visually-Impaired Users: An Evaluation of Official U.S. State and Territory COVID-19 Websites" (Hewitt & He, 2021), and "User Needs of Smart Home Services" (FakhrHosseini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Lectures incorporating this word include "User Experience and Evaluation." This word appeared frequently in conference proceedings titles such as "Tele-Technology Evaluation and User Testing with Persons Aging with Long-Term Mobility Disabilities" (Wu et al, 2021), "Internet Accessibility for Blind and Visually-Impaired Users: An Evaluation of Official U.S. State and Territory COVID-19 Websites" (Hewitt & He, 2021), and "User Needs of Smart Home Services" (FakhrHosseini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…According to WCAG criteria 1.4.3, text is required to have a contrast ratio of 4.5:1 and interactive components and large text are required to have a contrast ratio of 3:1 (Accessibility Guidelines Working Group, 2022). While this criterion is expected to be met by all web developers, our recent study found that 87% of official U.S. state and territory COVID-19 websites violated this guideline and contained content with insufficient text contrast (Hewitt & He, 2021). In the current study, we further investigated the effect of insufficient contrast on cognitive load and website usability if these errors remain uncorrected.…”
Section: Introduction Web Accessibility Researchmentioning
confidence: 90%
“…The stimulus websites were built using Wix's free website builder (https://wix.com). The websites were all based on COVID-19 informational sites, with their layouts and designs based on the best-performing sites from Hewitt & He (2021). Sites were hidden from search engine results to limit the potential of dated information spreading beyond experimental procedures.…”
Section: Apparatusmentioning
confidence: 99%
“…Three online web accessibility evaluation tools were employed: MAUVE++ [32], Siteimprove [33], and WAVE [34]. These tools have seen wide use in the literature [35][36][37][38][39][40] and all of them are listed by the W3C as appropriate for evaluation against the WCAG 2.1 guidelines [15]. More than one tool was utilized so that the assessment would benefit from more features and functionality and the limitations of each tool might be offset [41].…”
Section: Methodsmentioning
confidence: 99%